Apparent Color and Mechanical Properties of Industrial Sewing Threads Influenced by Thermal Treatment. (8th February 2021) - Huang, Wanzhen; Cao, Shengbin; Xu, Guangbiao
Abstract : The heat resistance of three kinds of industrial sewing threads used in the high-temperature environment was quantitatively studied, which could provide a reference to the application for the high-temperature environment. The effects of heat treatment time and heat treatment temperature on the apparent color and mechanical properties of modified polyphenylene sulfide and polytetrafluoroethylene, polytetrafluoroethylene, and modified polyphenylene sulfide sewing threads were discussed in this paper. It was found that the effect of heat treatment time on the apparent color and mechanical properties of these three kinds of sewing threads was relatively small, while the effect of heat treatment temperature on the apparent color and mechanical properties of these three kinds of sewing threads was significant. The apparent color and mechanical properties of polytetrafluoroethylene sewing thread were the least affected by heat treatment, followed by modified polyphenylene sulfide and polytetrafluoroethylene sewing thread; Polytetrafluoroethylene sewing thread could be used at a temperature of 250 °C, while modified polyphenylene sulfide and polytetrafluoroethylene and modified polyphenylene sulfide sewing thread could only be used at a temperature not exceeding 190 °C. The microstructure and infrared spectra of these three kinds of sewing threads were shown that when the heat treatment temperature was not less than 190 °C, the surface auxiliaries of modified polyphenylene sulfide fibers in modified polyphenylene sulfide and polytetrafluoroethylene and modified polyphenylene sulfide sewing threads were melt and decomposed at high temperature, and gather after cool, which made the surface auxiliaries distribution more uneven. Thus, the apparent color of modified polyphenylene sulfide and polytetrafluoroethylene and modified polyphenylene sulfide sewing thread became darker, and the mechanical properties decreased slightly.